Harnessing Electrochemical Processes for Enhanced Struvite Crystallization: A Comprehensive Review - Eko Ariyanto; Eka Sri Yusmartini; Gusmiatun Gusmiatun; Fatimah Fatimah; Mitayani Purwoko (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2025)
The recovery of nutrients from contaminated water and wastewater can effectively mitigate both the nutrient burden on water resources and the associated environmental issues affecting aquatic ecosystems. This approach presents a valuable solution towards achieving environmental and societal sustainability. Consequently, struvite crystallization technology has emerged as a promising method for nutrient recovery, as the resulting precipitate can be recycled as a natural fertilizer. This review aims to elucidate the characteristics of struvite and provide insight into the fundamental process of crystallization. Furthermore, it comprehensively discusses the various variables that influence struvite crystallization, with a special focus on its application in urine-contaminated water using electrochemical methods. The review also highlights the advantageous on environmental and economic aspects. In addition, the limitations of struvite crystallization technology are examined, and future research prospects are explored, particularly in the context of electrochemical techniques which offer innovative solutions for controlled nutrient extraction. Ultimately, this work serves as a foundational resource for the future utilization of struvite crystallization technology in nutrient recovery, in response to the escalating environmental challenges and depletion of natural resources.Keywords: Struvite formation, electrochemical process, magnesium anode, struvite crystallization, natural fertilizer